GLOBALISASI DAN PLURALISME HUKUM DALAM PEMBANGUNAN SISTEM HUKUM PANCASILA - Sunaryo Sunaryo (Faculty of Law, Universitas Diponegoro, 2013)
The presence of globalization brings new values in society and law is one subjects which cannot be separated from its impacts. The study of this law will discuss the development of the legal system of Pancasila in the of globalization era and legal pluralism. The results of the study of law can be concluded that in the globalization era, in the development of national law, required responsive legal order, and Pancasila has to be an ideal paradigm of law. Pancasila as ideal law, not only to be a filter but also to harmonize between global values and pluralistic local wisdom values which are followed and are believed to be the nation's way of life and ideology.